Teresa Moure’s Writing and Feminine Identity - Romero López, Alicia (Madrygal. Revista de Estudios Gallegos, 2015)
This brief study will explore how the key themes of Teresa Moure’s writing are developed in the 2005 essay A palabra das fillas de Eva and will chart their evolution in the 2012 publication Queer-emos un mundo novo. The investigation will also examine how the writer applies the theory of her essays to her fiction in the novel Herba Moura (2005).
Keywords: Teresa Moure; feminism; Herba Moura; feminine identity